2016
DOI: 10.1038/nmicrobiol.2016.190
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale analysis of the non-cultivable Treponema pallidum reveals extensive within-patient genetic variation

Abstract: Insights into the genomic adaptive traits of Treponema pallidum, the causative bacterium of syphilis, have long been hampered due to the absence of in vitro culture models and the constraints associated with its propagation in rabbits. Here, we have bypassed the culture bottleneck by means of a targeted strategy never applied to uncultivable bacterial human pathogens to directly capture whole-genome T. pallidum data in the context of human infection. This strategy has unveiled a scenario of discreet T. pallidu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
122
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(140 citation statements)
references
References 61 publications
(121 reference statements)
17
122
1
Order By: Relevance
“…However, research on virulence determinants of T. pallidum , and our understanding of protective immunity against it, have been hindered by our inability to culture the bacteria in vitro. To overcome this limitation, genome sequencing of T. pallidum directly from clinical samples is now possible 92,238 This advance should enable understanding of strain variation on a global scale, and help to identify outer membrane proteins and other surface antigens as possible vaccine candidates 81 . A recent study showed that immunization of rabbits with the lipoprotein TP071 prevented dissemination of T. pallidum and, hence, has become a promising vaccine candidate 81 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research on virulence determinants of T. pallidum , and our understanding of protective immunity against it, have been hindered by our inability to culture the bacteria in vitro. To overcome this limitation, genome sequencing of T. pallidum directly from clinical samples is now possible 92,238 This advance should enable understanding of strain variation on a global scale, and help to identify outer membrane proteins and other surface antigens as possible vaccine candidates 81 . A recent study showed that immunization of rabbits with the lipoprotein TP071 prevented dissemination of T. pallidum and, hence, has become a promising vaccine candidate 81 .…”
Section: Discussionmentioning
confidence: 99%
“…Of these, TprK (TP0897) has received the greatest attention because of its presumed role in immune evasion by the spirochete 87,88 ; it has been shown to undergo antigenic variation in seven regions believed to be extracellular loops harbouring B-cell epitopes 8992 . DNA sequence cassettes that correspond to V-region sequences in an area of the T. pallidum chromosome located away from the tprK gene have been proposed to serve as unidirectional donor sites for the generation of variable regions by nonreciprocal gene conversion 89 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The small amount of treponemal DNA within the only available sample of the 11q/j isolate (copy number less than 10 molecules of treponemal DNA per 1 μl) with an excessive amount of contaminating human DNA, which exceeded the treponemal DNA by at least 100,000 times, precluded the use of other techniques that have been recently reported to be effective in sequencing treponemal DNA directly from clinical samples [34, 35]. Efficient enrichment of treponemal DNA requires the number of treponemal copies > 1x10 4 per 1 μl [34].…”
Section: Discussionmentioning
confidence: 99%
“…Efficient enrichment of treponemal DNA requires the number of treponemal copies > 1x10 4 per 1 μl [34]. In fact, enrichment of the TEN Iraq B DNA sample, containing 10 4 copies per 1 μl, revealed genome coverage less than 12.4% [35].…”
Section: Discussionmentioning
confidence: 99%